Trends in management and outcomes of pulmonary embolism with a multidisciplinary response team. (3rd October 2022) - Chopard, R; Campia, U; Morin, L; Jering, K S; Almarzook, Z I; Snyder, J E; Rizzo, S; Waxman, A B; Goldhaber, S Z; Piazza, G
Abstract: Background: Multidisciplinary pulmonary embolism (PE) response teams have garnered widespread adoption given the complexities of managing acute PE and provide a platform for assessment of trends in therapy and outcomes. We aimed to describe temporal trends in PE management and outcomes following the deployment of such a team. Methods: All consecutive patients managed by our multidisciplinary PE response team activated by the Emergency Department were included over a 5-year calendar period. We examined temporal trends in management and rates of a composite primary endpoint (all-cause-death, major bleeding, recurrent venous thromboembolism, and readmission) at 30 days and 6 months. Results: We assessed 425 patients between 2015 and 2019. We observed an increase in PE acuity and use of systemic thrombolysis. The primary endpoint at 30 days decreased from 16.3% in 2015 to 7.1% in 2019 (adjusted rate ratio per period, 0.63; 95% CI, 0.47–0.84), driven by a decrease in the adjusted rate of major bleeding. Among 406 patients with complete follow-up, the adjusted rate ratio per year for the primary outcome at 6 months was 0.37 (95% CI, 0.19–0.71), driven by a decrease in all-cause mortality. Conclusions: We observed evidence of temporal changes in clinical presentation therapeutic strategies, and outcomes for acute PE, in parallel to, but not necessarily because of, the implementation of a multidisciplinary response team. Over time, major bleeding, mortality and readmission rates decreased, despite an increase in PE risk category. Funding Acknowledgement: Type of funding sources: None.